Analysis of Employee Work Posture at Sorting and Boiler Stations of PT Mitra Bumi Using the OWAS Method - Almahera, Piki; Chen, An; Sari, Resy Kumala; Adeswastoto, Hanantatur; Pratiwi, Nurul Dwi (Journal of Engineering Science and Technology Management (JES-TM), 2024)
Activities at sorting stations and boilers are high risk activities. Incorrect body posture, done repeatedly and relying on manual human power causes musculoskeletal disorders (MSDS). This research aims to analyze MSDs disturbances in body parts of workers at sorting  stations and boilers using the Ovako work posture analysis system (OWAS) method. OWAS can identify four body parts in a worker's posture, namely the back, upper arms, legs and weight category. Based on the results of the OWAS assessment, a score of  4144 was obtained at the sorting station, and 4141 at the boiler station. Both scores are in category 4, which means improvements need to be made as soon as possible. The injury risk index reached a value of 400 for both stations, indicating a very high level of danger.